Differences in kinematics of the support limb depends on specific movement tasks of take-off - Hojka, V.; Bacakova, R.; Kubovy, P. (Acta Gymnica, 2016)
Background: Many sport activities are a sequence of jumps (running, jumping, hurdling etc.). Each jump flight phase is the result of the execution of the previous support phase.